Keterkaitan Indikator Moneter Syariah Terhadap Pendapatan Domestik Bruto - Fitriani, Yunie; Aziz, Roikhan Mochamad; Amalia, Fitri (Signifikan: Jurnal Ilmu Ekonomi, 2012)
The purpose of this research is to analyze in the short term and long term between the four independent variables including: the financing of Islamic banking, the Jakarta Islamic Index (JII), the Islamic Bank Indonesia certificates (SBIS), and the money supply (JUB) to gross domestic product (GDP). This research uses the test to notice any indications of Granger was awarded a long-term relationship and Error Correction Model to see the existence of a short-term relationship. The result shows that in the short-run only SBIS that have a short-run relationship to GDP. In the long-run all the independent variables can explain the long-run relationship to GDPDOI: 10.15408/sjie.v1i1.2595